2021
DOI: 10.1002/adsc.202100214
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cleavage of Indoles Mediated by Urea Hydrogen Peroxide or H2O2 in Polar Solvents

Abstract: The oxidative cleavage of indoles (Witkop oxidation) involving the use of H2O2 or urea hydrogen peroxide in combination with a polar solvent has been described. Among these solvents, 1,1,1,3,3,3‐hexafluoroisopropanol (HFIP) stands out as the one affording the corresponding 2‐ketoacetanilides generally in higher yields The protocol described has also enabled the oxidation of different pyrroles and furans derivatives. Furthermore, the procedure was implemented in a larger‐scale and HFIP was distilled from the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…The pH decrease favors dissolution of silver nanoclusters @Ag and the formation of reactive oxygen species (ROS) (He et al 2011 , 2012 ; Rong et al 2018 ). The complicated redox processes, involving silver ions and silver nanoclusters, might explain the enhanced oxidation of Cys, Met, and Trp residues (Bellmaine et al 2020 ; Llopis et al 2021 ) observed in tryptic peptides originating from Procedures 1–4, compared to the level of Model D oxidation (ESM_Table S2). This phenomenon is particularly evident in the data for Procedure 3 executed in 2 M aqueous urea, which likely favors ROS-related oxidation as reported elsewhere (Yang et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pH decrease favors dissolution of silver nanoclusters @Ag and the formation of reactive oxygen species (ROS) (He et al 2011 , 2012 ; Rong et al 2018 ). The complicated redox processes, involving silver ions and silver nanoclusters, might explain the enhanced oxidation of Cys, Met, and Trp residues (Bellmaine et al 2020 ; Llopis et al 2021 ) observed in tryptic peptides originating from Procedures 1–4, compared to the level of Model D oxidation (ESM_Table S2). This phenomenon is particularly evident in the data for Procedure 3 executed in 2 M aqueous urea, which likely favors ROS-related oxidation as reported elsewhere (Yang et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a first attempt, NH‐free indolines were submitted to the oxidation reaction and as depicted in the Scheme 3, the conversions were quite good, but unfortunately, only a low percentage was due to the formation of the corresponding indole. Besides the product and indoline, different oxidation products, some of them coming from oxidative cleavage of indoles, [11a] were observed by NMR and GC‐MS. The fact of obtaining some conversion, encouraged us to run the reaction with the corresponding more nucleophilic N ‐methylated analogues.…”
Section: Methodsmentioning
confidence: 99%
“…Upon completion, the aqueous solution was extracted with dichloromethane and the organic layer was dried over MgSO4 and concentrated in vacuo. 7 .…”
Section: 456-tetrahydro-1h-(1)-benzazonin-27-dione (8)mentioning
confidence: 99%